e-ZAKAT4U program: enhancing zakat distribution system by merging with network-of-mosque (NoM) - Ahmad Dahlan, Abdul Rahman; Awang, Siti Nurasyikin; Mahmood, Afizah (Research Publish Journals, 2015)
The mosque has continuously played an active role in the guidance of the Muslim community, teaching both the young and older generations as well as producing a venue for Muslims to meet one another on religious occasions. But the mosque has much more potential than this, and it needs to be utilized fully so that many more areas of the lives of Muslims may benefit from it. The function of mosque can be divided into several parts which are as a community center, as a place of education, and as a place of worship. From here it shows that a mosque is not only focus onwership part but it covers all areas including as a centre for collecting zakat from individuals and receiving financial contribution from certain parties such as non-governmental institutions and individuals. In fact, mosque also received physical properties in a variety of shapes, including equipment until the land and buildings donated by certain parties (waqaf). Thus, when all contributions donated funds and properties are combined, then part of the mosque have the funds and property of great value which will be used as a source to contribute to the people especially the needy family. This project is proposed to increase the efficiency of zakat distribution in terms of less time consuming. For this project we choose Marang, Terengganu as the proof of concept.